2008
DOI: 10.1007/s11999-008-0279-3
|View full text |Cite
|
Sign up to set email alerts
|

Registry Outcomes of Unicompartmental Knee Arthroplasty Revisions

Abstract: Perceptions of the difficulty and outcome of unicompartmental knee arthroplasty revision (rev-UKA) vary. We analyzed differences in the complexity, cost, and survival of rev-UKAs compared with revision TKAs (rev-TKA). One hundred eighty knee arthroplasty revisions (68 rev-UKAs/112 rev-TKAs), defined as a minimum of tibial or femoral component revision, were identified from a community joint registry of 7587 knee implants performed between 1991 and 2005. Four of 68 rev-UKAs (5.9%) were revised a second time, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 23 publications
2
55
0
1
Order By: Relevance
“…Early survival studies of UKA demonstrated revision rates of 15% to 28% [23,34,44]. More recent articles report substantial increases in survival, with midterm survivorship for UKA of 84% to 98% (Table 1) [10,12,14,19,39,40,42,46,48,[57][58][59][60][61]. O'Rourke et al [43] followed by Price and Svard [49] documented long-term survival rates of UKA at 20 years of 84% and 91%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early survival studies of UKA demonstrated revision rates of 15% to 28% [23,34,44]. More recent articles report substantial increases in survival, with midterm survivorship for UKA of 84% to 98% (Table 1) [10,12,14,19,39,40,42,46,48,[57][58][59][60][61]. O'Rourke et al [43] followed by Price and Svard [49] documented long-term survival rates of UKA at 20 years of 84% and 91%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Satisfaction after either TKA or UKA is similar [54]. UKA has demonstrated survivorship of greater than 90% for more than 10 years after implantation in multiple studies [6,12,39,40,48,49,59]. The cumulative revision rate is higher for UKA than for conventional TKA, ranging from 82% to 98% at 5 to 22 years for UKA compared to 91% to 98.9% at 5 to 19 years for TKA (Table 1) [5, 6, 10, 12, 28-30, 33, 52].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have looked at the influence of these factors at a given time and not the trend in a longitudinal manner [15,18]. Moreover, the studies may be biased by including cases with traditionally poorer scores (revision for infection) [2,5,16] or less complex procedures (polyethylene liner exchange, patellar resurfacing, revision for unicondylar knee replacement) [6,10]. The aim of this study was to investigate the patterns of recovery after aseptic revision TKA in a prospective, longitudinal analysis of patients who underwent surgery in a tertiary referral unit.…”
Section: Discussionmentioning
confidence: 99%
“…However, few published studies have reported predictors of function after revision knee replacement and are limited by small sample size and therefore limited power to examine predictors of poor functional scores [15,18]. The studies that have looked at predictors include revisions for indications like infection, which traditionally have a poorer outcome [2,5,16], and also revisions for lesser interventions like polyethylene liner exchange, patellar resurfacings, and revision of unicompartmental knee replacements, which would have better outcomes [6,10] . Moreover, other than for the study by Ghomrawi et al [8], these studies have looked at predictors of outcome at a given time (cross-sectional analysis), rather than the trend over a period of time (longitudinal analysis).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, they also noticed that knee scores recovered in UKA revision patients when posterior cruciate ligament substituting designs were used. UKA revision knee replacement is a demanding operation; however, opinions vary on how it relates to primary TKA or TKA revision [7,16]. Saragaglia et al [22] evaluated the radiological and clinical results of 33 medial UKA converted to TKA revisions.…”
Section: Discussionmentioning
confidence: 99%